2015
DOI: 10.5713/ajas.15.0604
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Attitudes Toward Storing and Thawing Chicken and Effects of the Common Thawing Practices on Some Quality Characteristics of Frozen Chicken

Abstract: In this study, a survey was conducted to both evaluate the consumers’ general attitudes for purchasing and storing the raw chicken and determine the thawing practices used for defrosting frozen chicken at home. About 75% of the consumers indicated purchasing chicken meat at least once a week or more. Furthermore, the majority (82.16%) of those who stored at least a portion of the raw chicken stated freezing the raw chicken meat at home. Freezing the chicken meat was considered to have no effect on the quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…In contrast, L* for the samples subjected to MT, MUT, MIT, MAT, and MWT did not significantly differ from that for the fresh control (p > 0.05). This observation is similar to those reported by Anna [33] and Benli [36]. These authors demonstrated that thawing method had no significant influence on L*.…”
Section: Effect Of Thawing On Pork Colorsupporting
confidence: 92%
“…In contrast, L* for the samples subjected to MT, MUT, MIT, MAT, and MWT did not significantly differ from that for the fresh control (p > 0.05). This observation is similar to those reported by Anna [33] and Benli [36]. These authors demonstrated that thawing method had no significant influence on L*.…”
Section: Effect Of Thawing On Pork Colorsupporting
confidence: 92%
“…After the 7th month of freezing storage, however, the meat was characterized by more intense yellow colour (b * ) saturation than after the 1st month, irrespective of the thawing method applied. Studies conducted by Benli [34] on meat thawed using domestic methods and subjected to thermal treatment did not confirm changes in L * parameter of breast meat as well. Galobart and Moran [39] demonstrated that cooking thawed breast meat further increased L * value and reduced the differences in L * , a * , and b * parameters.…”
Section: Journal Of Food Qualitymentioning
confidence: 99%
“…Differences in the amount of thermal leakage between the different methods become less significant (p > 0.05) as the freezing storage period got prolonged. Benli [34] also demonstrated the impact of thawing methods on the volume of thermal leakage, but obtained lower thermal leakage in using microwave thawing and deep freeze processes, while obtaining higher leakage using tap water, warm water, and kitchen counter. Yu et al [28] confirmed that the volume of thermal leakage in frozen breast meat varied depending on the temperature while thawing.…”
Section: Journal Of Food Qualitymentioning
confidence: 99%
“…The consumption of poultry meat has increased over decades and has reached high levels worldwide [4,5]. Due to the growth in consumer demand for safe poultry products, chicken meat quality assessment and control has become a necessity [6].…”
Section: Introductionmentioning
confidence: 99%